Implementation of the Talaqqi Method in Memorizing Juz ‘Amma among Kindergarteners: A Case Study at Islamic Kindergarten, Banda Aceh - Fajriah, Heliati; Muthmainnah; Shalihah, Qatrun Nada (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study explores the implementation of the talaqqi method in Qur’anic memorization of Juz ‘Amma among kindergarten students at Baitussalihin Integrated Islamic Kindergarten in Banda Aceh. Although widely regarded as a foundational pedagogical approach in Islamic education, the talaqqi method remains understudied in early childhood contexts, particularly in relation to its interaction with home learning environments and parental support. The objective of this study is to examine how the talaqqi method is applied in classroom instruction, identify the supporting and inhibiting factors influencing its effectiveness, and assess the extent to which family-school collaboration affects children’s memorization outcomes. Employing a qualitative case study approach, data were collected through participatory observation and semi-structured interviews involving one principal, one teacher, one parent, and three students from Class B. Data were analyzed thematically using the Miles and Huberman interactive model. The findings reveal that while the talaqqi method was implemented systematically through phases of teacher recitation, student repetition (murājaʿah), and evaluation, its success was heavily influenced by contextual factors. Supporting elements included structured tahfīẓ programs, availability of auditory media, and parenting sessions. Inhibiting factors included inconsistent parental involvement, minimal follow-up at home, and difficulties in children’s articulation of makhārij al-ḥurūf. This study contributes to the growing literature on Qur’anic pedagogy by affirming that the effectiveness of talaqqi in early childhood education is not solely determined by instructional methods but also by the alignment between formal and informal learning contexts. Limitations of this study include its focus on a single institutional setting and reliance on qualitative data, which restrict generalizability. Future research should consider longitudinal or mixed-method designs to examine long-term memorization retention and the role of family engagement. Educators and curriculum developers are advised to integrate structured home-school communication mechanisms and provide training for parents in Qur’anic literacy facilitation.